Predictors of Precompetitive Anxiety: Differential Aspects in Runners in Route - Ruiz-Juan, Francisco; Universidad de Murcia (Pontificia Universidad Javeriana, 2015)
In sports, to study the dimensions of anxiety that involved in individual developing has become one of the key topics of the psychology of sport and exercise. The aim was to find out what had predictive relationships precompetitive anxiety about the commitment to run, run negative addiction, motivations and perceptions of success in road races. Participants 1795 runners en route (1105 Spaniards, Mexicans 690). Of these, 85.65% were men aged M = 38.98 (SD = 10.45) and 14.35% female, aged M = 37.88 (SD = 9.8). Data collection was conducted by adaptations to the Castilian Revised Competitive State Anxiety Inventory-2 (CSAI-2R), the Commitment to Running Scale-11 (CR-11), the Running Addiction Scale-8 (RAS-8 ) Motivations of Marathoners Scales Scales-34 (MOMS-34) questionnaire and Perception of Success Questionnaire (POSQ). Moderate levels of cognitive and somatic anxiety in both men and women and Spaniards and Mexicans were obtained; Also high values in confidence, significantly higher in men versus women and Mexicans with respect to Spanish. With slight differences by sex and country, anxiety could predict score higher in the less desirable psychological constructs analyzed (addiction, extrinsic motivation and guidance to ego), while self-confidence was the reverse, that is, by value in as far as the most desirable psychological constructs (commitment and more self-determined motivation).